Comparative study of earthworm communities, microbial biomass, and plant nutrient availability under 1-year Cajanus cajan (L.) Millsp and Lablab purpureus (L.) Sweet cultivations versus natural regrowths in a guinea savanna zone - Koné, Armand W.; Edoukou, Ettien F.; Tondoh, Jérôme E.; Gonnety, JT; Angui, Pascal K.T.; Masse, D (Springer, 2012)
In tropical savannas where soils are generally sandy and nutrient poor, organic farming associated with enhanced soil biological activity may result in increased nutrient availability. Therefore, legumes have been introduced in the humid savanna zone of Côte d’Ivoire, owing to their ability to fix atmospheric N and to continually supply soil with great quantity of organic materials in relatively short time. The main objective of this study was to assess the influence of two legume (Cajanus cajan and Lablab purpureus) cultivations on earthworm communities and P and N availability. Trials were carried out under farmers' field conditions; C. cajan was planted on savanna soils (trial 1) while L. purpureus was established on new Chromolaena odorata-dominated fallow soils (trial 2). Native vegetations were considered as controls. Changes in soil properties (earthworm abundance and diversity, microbial biomass carbon (MBC), and plant available P and N) were assessed using the biosequential sampling. After 1 year, both the legume stands showed a significantly higher density of earthworms, compared with the respective controls. This trend was linked to an increase in the abundance of the detritivores Dichogaster baeri Sciacchitano 1952 and Dichogaster saliens Beddard 1893, and the polyhumic Stuhlmannia zielae Omodeo 1963. Equally, legume had beneficial impacts on the average number of earthworm species, the Shannon–Weaver index of diversity and MBC in savanna (trial 1). Available P and ammonium significantly increased under both legume cultivations and were significantly and concurrently linked to litter quality and earthworm activities as shown by multiple regressions. As a result, legumes could improve nutrient availability in the sandy soils of central Côte d’Ivoire by positively affecting soil biological activity and this could bring farmers to cultivate crops on savanna lands.